PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ela Widasari; Mega Furwanti (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2020)
This research was conducted with the aim of knowing that the Financial Performance and Company Size can affect the Firm Value of the LQ45 Companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The method used in this research is quantitative research methods. The population used is all LQ45 companies listed on the Indonesia Stock Exchange (BEI) using purposive sampling method. Data collection obtained through secondary data. The data analysis technique used in this research is the Classical Assumption Test which consists of (Normality Test, Heteroscedasticity Test, Multicollinearity Test and Autocoleration Test), Multiple Linear Regression Analysis Test, Correlation Analysis Test, Determination Coefficient Test, and Hypothesis Test which consists of ( Statistical t test and statistical test F).The result of t statistical test shows that the Financial Performance as X1 has a value of "t" _ "count" "t" _ "table", namely 2.053 1.99601 with a significance level of 0.044 0.05, this means that H0 is rejected and H1 is accepted so that Financial Performance (X1) has a partial effect on Firm Value Company Size as X2 has a tcount ttable where the result is -0.234 1.99601 with a significance level of 0.816 0.05, p. This means that H0 is accepted and H2 is rejected, so Company Size has no partial effect on Firm Value. And the test results based on the F statistical test in this study were obtained with Fcount Ftable, namely 3,424 3.13 with a significant level of 0.038 0 , 05. It can be concluded that H0 is rejected and H3 is accepted. Thus, Financial Performance and Firm Size have a joint or simultaneous effect on Firm Value.